A Companion Diagnostic With Significant Clinical Impact in Treatment of Breast and Gastric Cancer - Jørgensen, Jan Trøst; Winther, Henrik; Askaa, Jon; Andresen, Lena; Olsen, Dana; Mollerup, Jens (Frontiers in Oncology, 2021)
The development of trastuzumab (Herceptin®) was one of the most significant cancer drug development projects of the 20th century. Not only was it a scientific and medical achievement but it also paved the way for the drug-diagnostic codevelopment model, where a predictive biomarker assay is developed in parallel to the drug. One of the challenges in the development of trastuzumab was to select the right patient population likely to respond and here, it was critical to have access to an accurate, robust and reliable assay for detection of HER2 overexpression in tumors. In the clinical development of trastuzumab, a clinical trial assay (CTA), developed by Genentech, was used for selection of HER2 positive patients. However, during the phase III trial with trastuzumab, a new optimized IHC assay, HercepTest™ was designed and developed by Dako. In the final stage of its development, a comparative study with the CTA was conducted in order to show concordance between the two assays. In September 1998, the Food and Drug Administration (FDA) simultaneously granted approval to trastuzumab and HercepTest™. The assay has been used for patient selection in a number of significant breast cancer clinical trials such as the HERA, CLEOPATRA, EMILIA and more. In these trials, HercepTest™ demonstrated its clinical utility in the neoadjuvant, adjuvant, and metastatic setting as well as in relation to different types of HER2 targeted therapies. Likewise, the assay was used for selection of HER2 positive gastric cancer patients in the important ToGA trail. HercepTest™ was the first companion diagnostic ever approved by the FDA, and more than 20 years use has documented its clinical impact.